FC019: Parietal Epithelial Cells Activation During Gemcitabine-Induced Nephrotoxicity: Communication With Endothelial Cells?. (3rd May 2022) - Ben Ali, Chloé; Lafargue, Marie-Camille; Morvan, Marion; Van Wynsberghe, Margaux; Audard, Vincent; Sahali, Dil; Hénique, Carole
Abstract: BACKGROUND AND AIMS: Gemcitabine (GEM) is an anticancer drug, indicated in the treatment of several types of solid cancers such as pancreatic, breast, bladder cancer, etc. This molecule is effective in tumor processes but causes adverse effects on other organs, including the haematopoietic system and the kidney. The renal toxicity of gemcitabine is illustrated by thrombotic microangiopathy (TMA), whose onset is dramatic and associated in more than 97% of cases with acute renal failure. This adverse effect induces discontinuation of treatment with negative consequences on tumor control. It is, therefore, essential to understand the pathophysiological mechanisms of gemcitabine nephrotoxicity. TMA at the glomerular level reflects damage to the endothelial cell (ECs). However, previously, data of our team show that other glomerular cells, parietal epithelial cells (PECs), could be involved in these lesions. Thus, in this project, we want: i) to describe the modifications of the PEC and EC proteome exposed to gemcitabine and ii) to analyse PEC and EC secretome exposed to gemcitabine and to study the cell communication between PECs and ECs. METHOD: In our in vitro experiments, we used a murine PEC cell line and a murine EC cell line. The PECs are exposed to 100 μM GEM for 24-h and the culture supernatants are recovered. These PEC supernatants are used in conditioned media experiments to expose ECs for 24-h. On the other hand, ECs were directly exposed to 1 μM GEM for 24-h and culture supernatants were also recovered. Analyses of protein expression are carried out by western blot and immunofluorescence staining. RESULTS: When PECs are exposed to GEM (100 µM, 24-h), we observe an increase in apoptosis (caspase 3 cleavage) as well as DNA damage (γH2AX). However, PECs specific markers, such as PAX2 and Claudin-1, do not appear to be affected. Our results also show an increase in the expression of the transcription factor CHOP and the chaperone protein BIP, suggesting the presence of endoplasmic reticulum (ER) stress in PECs exposed to gemcitabine. In order to study cell communication between PECs and ECs, we set up conditioned media experiments. We first studied the expression of different endothelial markers on ECs exposed to PEC supernatants. The expression of the endothelial markers such as E-cadherin, CD31 and PDGFRβ decreases compared with control cells when ECs are exposed to PEC supernatants. Actin cytoskeleton reorganization is also observed with an increase in cortical actin. Moreover, the microtubule network seems to be also affected with a tendency to decrease tubulin expression. Finally, there is an increase in γH2AX suggesting the presence of DNA damage in ECs exposed to PEC supernatant. The next experiments aim at identifying the factors responsible for this cell communication (proteins, lipid mediators, non-coding RNA, extracellular vesicles). CONCLUSION: Our results show GEM has a direct effect on PECs (apoptosis, DNA damage, ER stress). In addition, we show the effect of PEC supernatants exposed to GEM on ECs (decrease in endothelial markers, cytoskeleton modifications, DNA damage).